Survival of elderly patients with multiple myeloma: effect of upfront autologous stem cell transplantation - Merz, Maximilian; Hillengaß, Jens; Dreger, Peter; Brenner, Hermann; Goldschmidt, Hartmut (European journal of cancer, 2016)
Background: The aim of this study was to determine the value of upfront autologous transplantation (ASCT) in elderly patients (60-79 years) with myeloma. Methods: We analysed relative survival (RS) of patients diagnosed in 1998-2011 and treated with ASCT within 12 months after diagnosis in Germany (n = 3591; German Registry of Stem Cell Transplantation) and compare RS with survival of myeloma patients diagnosed in the same years in Germany (n = 13,903; population-based German Cancer Registries). Results: Utilisation of ASCT has increased rapidly between 2000-2002 and 2009-2011 (60-64years: 7.0-43.0%; 65-69 years: 6.6-23.7%; 70-79 years: 0.4-4.0%). Comparison of 5-year RS of patients from the general German myeloma population who have survived the first year after diagnosis with 5-year RS of patients treated with ASCT revealed higher survival for transplanted patients among all age groups (60-64: 59.2% versus 66.1%; 65-69: 57.4% versus 61.7%; 70-79: 51.0% versus 56.6%). RS increased strongly between 2003-2005 and 2009-2011 for the general German myeloma population (+8.5%) and for patients treated with ASCT (+11.8%). Differences in RS between these groups increased over time from +1.9% higher age-standardised survival in transplanted patients in 2003-2005 to 5.2% higher survival in 2009-2011. Conclusion: We conclude that upfront ASCT might be a major contributor to improved survival for elderly myeloma patients in Germany.